YUSUF HAS HACIP'S IDEAL MANAGEMENT MODEL: SCALE DEVELOPMENT STUDY - Şen, Alper Tunga; Turan, Erol; Özdemir, Adem; Kundakçı, Deniz; Savi, Fatma Zehra (Kafkas Universitesi Iktisadi ve Idari Bilimler Fakultesi Dergisi, 2025)
Management is one of the most researched subjects in social sciences. Management science is increasingly gaining attention in the literature because it is a broad field where various management models are constantly investigated, and scientists try to obtain better and more effective solutions. However, the number of researchers who carry out studies to develop new management models is low. This study, which includes both qualitative and quantitative methods, is an attempt to develop a management model scale based on Yusuf Has Hacip's work Kutadgu Bilig. Various processes were carried out during the development phase, including item generation, scale improvement, Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA) and validation process. The results revealed that the Yusuf Has Hacip (YYH) Ideal Management Model Scale has four sub-dimensions: law and justice, wisdom, destiny and satisfaction and happiness and status. The goodness-of-fit indices obtained as a result of confirmatory factor analysis can be listed as Chi-Square (CMIN)/Degrees of Freedom (FD)=1.678, Comparative Fit Index (CFI)=0.97, Root Mean Square Error of Approximation (RMSEA)=0.041, Standardized-Root Mean Square Residual (SRMR)=0.048 and Goodness of Fit Index (GFI)=0.95. These obtained values show that the semantic and structural validity of the developed scale is accepted.